2019
DOI: 10.2224/sbp.7718
|View full text |Cite
|
Sign up to set email alerts
|

Gender-dependent difference in the relationship between pain aspects and pain catastrophizing

Abstract: We examined the gender dependence of the relationships between sensory and affective pain and pain catastrophizing. Study participants were 170 people who were receiving treatment for chronic pain at a university pain clinic in Daegu, Republic of Korea. For men, higher levels of sensory pain were associated with greater pain catastrophizing at low and average levels of affective pain, but not at a high level of affective pain. For women, higher levels of affective pain were associated with greater pain catast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…18,19 On the basis of previous research, age, sex, and pain duration were tested as potential covariates for the cross-lagged panel analysis. [33][34][35][36][37] In the present sample, only sex was significantly associated with pain catastrophizing and was therefore included as a covariate in the model.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…18,19 On the basis of previous research, age, sex, and pain duration were tested as potential covariates for the cross-lagged panel analysis. [33][34][35][36][37] In the present sample, only sex was significantly associated with pain catastrophizing and was therefore included as a covariate in the model.…”
Section: Discussionmentioning
confidence: 99%
“…Cross-lagged panel analyses allow for the estimation of the directional influence between variables over time, controlling for autoregressive and synchronous effects 18,19 . On the basis of previous research, age, sex, and pain duration were tested as potential covariates for the cross-lagged panel analysis 33–37 . In the present sample, only sex was significantly associated with pain catastrophizing and was therefore included as a covariate in the model.…”
Section: Methodsmentioning
confidence: 99%
“…Catastrophizing was found to be associated with pain behavior, health care use, hospital stay, and analgesic drug use. Several studies have reported that females experience more catastrophizing than males (15). Catastrophizing is correlated with increased pain experience and increases pain intensity up to 7% to 31% (16).…”
Section: Introductionmentioning
confidence: 99%